2023
DOI: 10.1186/s40104-023-00840-5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary bamboo leaf flavonoids improve quality and microstructure of broiler meat by changing untargeted metabolome

Abstract: Background Dietary bamboo leaf flavonoids (BLFs) are rarely used in poultry production, and it is unknown whether they influence meat texture profile, perceived color, or microstructure. Results A total of 720 one-day-old Arbor Acres broilers were supplemented with a basal diet with 20 mg bacitracin/kg, 50 mg BLFs/kg, or 250 mg BLFs/kg or without additions. Data showed that the dietary BLFs significantly (P < 0.05) changed growth performance and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Numerous studies have shown that secondary metabolites such as flavonoids, polyphenols and polysaccharides in feeds exhibit good tolerance in improving meat quality and coping with abiotic stress ( Cao et al, 2023 ; Catarino et al, 2023 ; Chen et al, 2023 ; Zhao et al, 2023 ). In this experiment, it was surprising to note that the GG group exhibited significant differences in terms of its crude polysaccharides, polyphenols and flavonoid content compared with the HG group ( P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that secondary metabolites such as flavonoids, polyphenols and polysaccharides in feeds exhibit good tolerance in improving meat quality and coping with abiotic stress ( Cao et al, 2023 ; Catarino et al, 2023 ; Chen et al, 2023 ; Zhao et al, 2023 ). In this experiment, it was surprising to note that the GG group exhibited significant differences in terms of its crude polysaccharides, polyphenols and flavonoid content compared with the HG group ( P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the dietary fiber in bamboo powder promotes gut health by activating specific ORs in the gut microbiota during fiber fermentation. This, in turn, enhances nutrient digestion and absorption ( Yang et al, 2019 ; Cao et al, 2023 ), bamboo powder offers a sustainable and economically viable option for improving poultry nutrition while providing nutritional benefits and supporting overall health.…”
Section: Introductionmentioning
confidence: 99%